2018
DOI: 10.1377/hlthaff.2017.1505
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act’s Marketplaces Expanded Insurance Coverage For Adults With Chronic Health Conditions

Abstract: The Affordable Care Act (ACA) made private nongroup health insurance more accessible to nonelderly adults with chronic conditions, with enrollment growth occurring through the federal and state-based Marketplaces. During the July through December reference period in 2014-15, 45 percent of Marketplace enrollees ages 18-64 were treated for chronic conditions, compared with 35 percent of non-Marketplace nongroup enrollees and 38 percent of adults with employer-sponsored insurance. Marketplace enrollees also had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…22 Participation in the individual market roughly doubled following implementation of the ACA's Marketplaces and subsidies, provisions to stabilize the individual market, the individual mandate, and outreach efforts starting in 2014. 20,23 Four years into the operation of the ACA Marketplaces, this study found worse reported experiences among off-Marketplace enrollees than among on-Marketplace enrollees, who expressed less difficulty finding the best or most affordable option despite receiving less inperson assistance than off-Marketplace shoppers. Differences in the shopping contexts on and off Marketplace might explain these results.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…22 Participation in the individual market roughly doubled following implementation of the ACA's Marketplaces and subsidies, provisions to stabilize the individual market, the individual mandate, and outreach efforts starting in 2014. 20,23 Four years into the operation of the ACA Marketplaces, this study found worse reported experiences among off-Marketplace enrollees than among on-Marketplace enrollees, who expressed less difficulty finding the best or most affordable option despite receiving less inperson assistance than off-Marketplace shoppers. Differences in the shopping contexts on and off Marketplace might explain these results.…”
Section: Discussionmentioning
confidence: 76%
“…Particular subgroups of individual market enrollees (those in families with chronic conditions and those with low health insurance literacy) had higher rates of negative experiences when choosing a health plan compared to their healthy and more insuranceliterate counterparts. Both chronic conditions and poor health insurance literacy are common among shoppers in the individual market, 4,23,25 which places large numbers of enrollees at risk for poor experiences and negative downstream effects-including unmet health care need due to cost and negative health outcomes. 2,9 However, for enrollees in families with chronic conditions, those who purchased a plan through the Marketplace were significantly less likely to report negative shopping experiences than those purchasing plans off Marketplace.…”
Section: Discussionmentioning
confidence: 99%
“…From 2014 to 2016, the number of uninsured dropped from 16% to 11%. Studies have demonstrated higher rates of insurance among patients with chronic conditions, cancer survivors, and newly diagnosed patients with cancer . Using data from the NHIS from 2010 to 2016, Nipp et al.…”
Section: Impact Of Ppaca On the Reduction Of Uninsuredmentioning
confidence: 99%
“…18 Additionally, those health exchange-insured compared with other privately insured were more likely to have chronic conditions and higher rates of service use. 19 Having more adults insured reduced the risk of medical debt and deferred needed medical care among all privately insured, most of whom have no/ low-deductible insurance. However, HD insured and vulnerable-though benefi ting from improved access to care through insurance coverage-are signifi cantly more likely to report medical debt and deferred needed medical care then other insured.…”
Section: Discussionmentioning
confidence: 99%